2013
DOI: 10.1158/1940-6207.capr-12-0501
|View full text |Cite
|
Sign up to set email alerts
|

DNA Methylation Biomarkers for Noninvasive Diagnosis of Colorectal Cancer

Abstract: DNA methylation biomarkers for noninvasive diagnosis of colorectal cancer (CRC) and precursor lesions have been extensively studied. Different panels have been reported attempting to improve current protocols in clinical practice, although no definite biomarkers have been established.In the present study, we have examined patient biopsies starting from a comprehensive analysis of DNA methylation differences between paired normal and tumor samples in known cancer-related genes aiming to select the best performi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
70
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 113 publications
(80 citation statements)
references
References 46 publications
5
70
0
1
Order By: Relevance
“…22). Pyrosequencing assays were designed to analyze and validate the results obtained from the WGBS data at intragenic DMRs, and to analyze DNA methylation levels in human breast cancer samples (23). Bisulfite-genomic sequencing (24) was carried out to validate DNA methylation at DMRs overlapping transcription start site-proximal regions.…”
Section: Dna Methylation Analysesmentioning
confidence: 99%
“…22). Pyrosequencing assays were designed to analyze and validate the results obtained from the WGBS data at intragenic DMRs, and to analyze DNA methylation levels in human breast cancer samples (23). Bisulfite-genomic sequencing (24) was carried out to validate DNA methylation at DMRs overlapping transcription start site-proximal regions.…”
Section: Dna Methylation Analysesmentioning
confidence: 99%
“…Besides, the AGTR1 promoter methylation is associated with oral squamous cell carcinoma (OSCC) development (12). And AGTR1 was also validated in stool DNA with a high detection sensitivity for noninvasive diagnosis of colorectal cancer (13). In addition, DNA methylation microarray datasets showed that methylation of AGTR1 might be an effective biomarker for NSCLC diagnosis (17).…”
Section: Introductionmentioning
confidence: 99%
“…Slit levels dramatically decrease in the midgut of Atg16 WD40 and Rab19 mutant flies, similar to IBD patients with decreased Slit expression due to promoter hypermethylation (Lobatón et al, 2014). Interestingly, Slit promoter hypermethylation in IBD patients is associated with an increased risk of cancer (Carmona et al, 2013). Notably, Atg16 WD40 mutations also lead to an early dysplasia-like gut phenotype in adult flies.…”
Section: Discussionmentioning
confidence: 99%